PERAN KURIKULUM LEADERSHIP DALAM PEMBENTUKAN KARAKTER - Amiruddin, Amiruddin; Marwan, Marwan; Ramasepa, Nuzlita; Salehha, Osey Putri (Hijri, 2023)
Education is an important sector in national development that aims to educate the nation's life and improve the quality of human life. Education cannot be carried out without a curriculum. The curriculum can be implemented in educational units called schools. SA school is a place for students to develop their full potential. This study aims to determine the role of the leadership curriculum in character building at the Bireuen Nature School (SABIR). The approach used in this research is a qualitative approach with a descriptive type. Data collection techniques using observation, interviews,and documentation. The results of the study show that: the leadership curriculum is carried out by students at any time; the leadership curriculum makes students better understand the relationship between humans and humans, and humans and their God through indicators of the discipline of worship to the relationship between humans and their environment; the leadership curriculum is decisive in character building at the Bireuen Nature School.Keywords:Leadership Curriculum, Character Formation, Natural School